2019
DOI: 10.1021/acschembio.9b00289
|View full text |Cite
|
Sign up to set email alerts
|

The Clinically Used Iron Chelator Deferasirox Is an Inhibitor of Epigenetic JumonjiC Domain-Containing Histone Demethylases

Abstract: Supporting Information available: This material is available free of charge via the internet. It includes further enzyme inhibition data (MS), enzyme kinetic analyses, detailed EPR spectroscopic analyses, NMR binding experiments of control compounds, docking structures, as well as further analyses of the cellular effects of deferasirox (cell proliferation, western blots, immunostaining). Additional experimental methods are presented. AUTHOR INFORMATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
(184 reference statements)
1
18
0
Order By: Relevance
“…18,68 Interestingly, in this assay the extracellular iron chelator DFX functions as a pan-HI, in contrast to its reported PHD-selectivity under some conditions 26,52 ; note more recent work indicates DFX and related compounds are unlikely to be selective for the PHDs. 57 DM-NOFD showed no inhibition of FIH toward OTUB1 HD formation, but interestingly nevertheless regulated HIF transactivation activity in agreement with previous reports. 7,26 A possible explanation is that the sensitivity of FIH to DM-NOFD depends on its protein substrate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…18,68 Interestingly, in this assay the extracellular iron chelator DFX functions as a pan-HI, in contrast to its reported PHD-selectivity under some conditions 26,52 ; note more recent work indicates DFX and related compounds are unlikely to be selective for the PHDs. 57 DM-NOFD showed no inhibition of FIH toward OTUB1 HD formation, but interestingly nevertheless regulated HIF transactivation activity in agreement with previous reports. 7,26 A possible explanation is that the sensitivity of FIH to DM-NOFD depends on its protein substrate.…”
Section: Discussionsupporting
confidence: 92%
“…Typically, most reported HIs, including those in clinical evaluation, are PHD active site iron chelators or 2OG analogs/competitors, though it should be noted that compounds chelating Fe in solution also induce HIF as well as inhibiting other 2OG-dependent oxygenases. 25,57 Because both iron and 2OG are important for cellular energy metabolic homeostasis, we analyzed if the HIs affect cellular energy metabolism under standard cell culture conditions. Extracellular lactate and glucose as well as intracellular ATP levels were quantified in the same HEK293-or Hep3B-derived samples, respectively, following 22 hours of HI treatment.…”
Section: The Majority Of His Do Not Change Cellular Energy Metabolimentioning
confidence: 99%
“…All cellular stresses induced alterations to the global histone PTM profiles, but to different extents, as revealed by our LC-MS-based analyses of intact histones. Note, we have recently shown that Exjade also causes alterations in histone PTMs, at least in part through inhibition of the JmjC KDMs [30]. The dose-and time-dependencies of these effects were investigated to gain further insight into the effects of hypoxic/ hypoxia-mimetic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…More specific PHD inhibitors, such as IOX2 and FG4592 (Roxadustat, which has been approved for use in some countries and is in late stage clinical trials in others for treatment of renal anaemia) [27,28], are used to replicate aspects of reduced oxygen availability on PHD activity. Hypoxia and hypoxia mimetics are reported to affect epigenetic regulation by changing the activities of histone modifying enzymes and the levels of HIF isoforms [8,12,29,30]. However, differences between the effects of hypoxia and hypoxia mimetics on the levels of histone PTMs have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…A small molecule UNC2170 inhibits 53BP1 binding at the interface of two Tudor domains of a 53BP1 dimer, showing cellular activity by suppressing class switch recombination [173]. Recent research shows that the clinically used iron chelator deferasirox potently inhibit JMJD2A, leading to a high level of histone trimethylation and inhibition of cancer cell growth [174]. What is more, UHRF1 inhibitors as an alternative of DNA demethylation agents can inhibit DNA methylation in cancer therapies [175].…”
Section: Bmt and Tudor Inhibitorsmentioning
confidence: 99%